Relationship between Views of Progressivism and Curriculum 2013 on Mathematics Learning - Rachmawati, Intan (Universitas Sebelas Maret, 2019)
Progressivism is one of the streams that can contribute and require problem solving in mathematics learning. Progressivism supports changes for the better that prioritize students and develop various student abilities in the implementation of learning. Educational programs that prioritize students in the progressivism view of the curriculum. The 2013 curriculum is a learning system renewal that is expected to further develop the potential of students. The 2013 curriculum requires students who are passive to be active in order to solve problems in learning mathematics. The implementation of the 2013 curriculum changes previous learning activities towards a learning system more advanced so that students' ability to solve math problems can develop. This article aims to determine the relationship between progressivism views and the 2013 curriculum on mathematics learning. This article uses a literature study method. This data is obtained from some of the research results contained in books, journals, and proceedings that are related to the title of the article. The results show that the viewpoint of progressivism is interrelated with the 2013 curriculum in mathematics learning. Progressivism can make a major contribution to the development and progress in the implementation of the 2013 curriculum, it can be seen from the relationship between the two wanting a change in the learning process so that it focuses more on students.